'Tonality, clarity, strength': gesture, form, and Nordic identity in Carl Neilsen's piano music - Grimley, D (Oxford University Press, 2005)
Identifying elements of a Nordic subjectivity in the music of Carl Nielsen is a complex exercise. As Naomi Cumming has observed, we construct musical subjectivity in multiple ways, some of which we perceive as a 'composer's voice'. But musical identity is properly a tension between compositional process, reception, and historical context. Carl Nielsen's piano music has been less widely acknowledged outside Denmark than his symphonies, but offers a compelling case study in the formation of music subjectivity. His piano works employ a diverse range of different compositional strategies, from stylized neo-Baroque textures to angular modernist dissonance and the carnivalesque juxtaposition of different musical characters or voices. The critical reception of his piano music reveals interesting trends in the construction of a Danish musical style. This essay presents a general survey of his major piano works, from the Symphonic Suite to the posthumous Three Piano Pieces, and seeks to place them in their European historical context.